Beyond Digital Literacy: Exploring Factors Affecting Digital Performance of University Staff - Carmen Koch; Fiona Fehlmann (Media and Communication)
Digital literacy is essential but doesn’t guarantee digital performance. Many researchers consider factors such as attitude, cultural environment, or institutional setting in their frameworks when researching digital literacy. Yet, their significance often gets lost in a catalog of required skills and knowledge. Here we develop a model outlining factors influencing university personnel’s digital performance across diverse tasks, and we discuss associated challenges. The model derives from literature and insights from 20 qualitative interviews with academic staff in teaching, research, or consulting roles. Results show that institutional settings and employee empowerment are pivotal in shaping openness to digital tools. Intentions fail due to resource constraints and lack of recognition, leading to limited experience with digital opportunities. Well-being significantly influences willingness to embrace digital resources amidst the balancing act of anticipating future efficiency against investing time and resources. Maintaining a team atmosphere often results in alignment with the least digitally competent. With appropriate conditions, time resources, and support, staff could efficiently utilize digital resources, even with only basic skills, which fosters the integration of all workforces. We argue for comprehensive assessments of university employees’ digital performances, considering context and holistic aspects beyond personal skills and knowledge. Our model encompasses digital literacy, openness to digital developments, digital culture, primary conditions, services/empowerment offerings, and mindfulness.